Karakterisasi Kimia dan Efek Hipoglikemik Beras Analog Berbahan Dasar Jagung, Sorgum, dan Sagu Aren - Slamet Budijanto; Yanica Ivory Andri; Didah Nur Faridah; Santi Noviasari (Faculty of Agricultural Technology, Universitas Gadjah Mada, Yogyakarta, Indonesia, 2017)
Rice analogue is an alternative food similar to rice which is made from other sources of carbohydrate apart from rice. This research was aimed to determine the glycemic index (GI) value and chemical characteristic (total phenolics content and dietary fiber) of rice analogues made from: (1) corn, sorghum, and arenga starch (rice analogue A): (2) corn and arenga starch (rice analogue B). GI was tested in human blood samples and was determined by the comparison of curve area between food sample (analogues rice) and standard (25 g glucose) which was equivalent to 25 g of carbohydrates. The GI values of Rice analogue A and B were 47,09 and 52,31 respectively. Both were considered as low GI foods. The low GI values were due to the phenolic compounds and dietary fiber contained in the rice analoguesAnalogue rice was an alternative food similar to rice which is made from carbohydrate sources beside of paddy. This research were aimed to determine the glycemic index (GI) value and to quantify chemical characterization (total phenolics content and dietary fiber) of analogues rice made from 1) corn, sorghum, and arenga starch (analogue rice A) and 2) corn and arenga starch (analogue rice B). GI was tested by human blood samples and determined by area under the curve for test food (analogues rice) which is equivalent to 25 grams of carbohydrates and area under the curve for the reference food (25 grams of glucose) compared. Analogue rice A has 47.09 GI value, whilst analogue rice B has 52.31 GI value. Both were grouped into low GI food. A low GI value was due to the phenols compounds and dietary fiber contained in the analogues rice. ABSTRAKBeras analog merupakan pangan alternatif mirip beras yang dibuat dari sumber karbohidrat selain padi. Penelitian ini bertujuan untuk menentukan nilai indeks glikemik (IG) dan karakterisasi kimia (total fenolik dan serat pangan) pada beras analog berbahan baku: (1) jagung, sorgum, dan sagu aren (beras analog A); (2) jagung dan sagu aren (beras analog B). Pengujian IG menggunakan sampel darah manusia dan ditentukan dengan membandingkan luas area kurva antara sampel pangan (beras analog) dan standar (25 g glukosa) yang setara dengan 25 g karbohidrat. Beras analog A memiliki nilai IG sebesar 47,09, sedangkan beras analog B memiliki IG sebesar 52,31. Kedua beras analog termasuk dalam kategori pangan IG rendah. Rendahnya nilai IG dikarenakan adanya komponen fenol dan serat pangan yang terkandung pada beras analog.